2021
DOI: 10.1055/s-0041-1725013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency and West Syndrome: An Uncommon but Preventable Cause of Neurological Disorder. Report on Three Cases, One of Them with Late Onset during Vitamin B12 Treatment

Abstract: Vitamin B12 is a water-soluble vitamin that plays a fundamental role as an essential cofactor for two enzymes responsible for the production of succinyl-CoA and methionine. Vitamin B12 deficiency can occur in infants and may be related to the breastfeeding mother's adherence to a vegan diet or somatic diseases in the mother. It should be differentiated from inborn errors of vitamin B12 metabolism. Herein, we report the cases of three infants with West syndrome; all three were breastfed by mothers who followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Furthermore, 25 innate metabolic errors resulting from single mutated genes cause heterogeneous conditions and may contribute to the etiology of IS [ 28 ]. Vitamin B12 deficiency results in severe neurological symptoms such as seizures and spasms, which gradually improve with vitamin B12 supplementation [ 29 ]. In this study, metabolic abnormalities were identified as a risk factor for non-etiology-specific IS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 25 innate metabolic errors resulting from single mutated genes cause heterogeneous conditions and may contribute to the etiology of IS [ 28 ]. Vitamin B12 deficiency results in severe neurological symptoms such as seizures and spasms, which gradually improve with vitamin B12 supplementation [ 29 ]. In this study, metabolic abnormalities were identified as a risk factor for non-etiology-specific IS.…”
Section: Discussionmentioning
confidence: 99%
“…As in our case, the most common symptoms include hypotonia and brisk reflexes, irritability or lethargy, and developmental delay and even regression. Epileptic seizures and movement disorders have been described [ 2 , 3 , 4 , 5 , 11 , 12 ]. However, as the neurological symptoms are nonspecific, the first-line diagnostic work-up usually also includes a brain MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In case of vitamin B12 deficiency, it may have permanent effects on neuronal (West syndrome, peripheral neuropathy, etc. ), hematological and cognitive levels, which may be irreversible due to the deterioration in these developmental processes [1,2]. Vitamin B12 deficiency in adolescents leads to several disorders including mood and behaviour changes, neurological and hematological disorders and decrease in cognitive functions [1].…”
Section: Introductionmentioning
confidence: 99%